Phosphatidylinositol 3-Phosphate 5-Kinase, FAB1/PIKfyve Kinase Mediates Endosome Maturation to Establish Endosome-Cortical Microtubule Interaction in Arabidopsis. Issue 3 (9th September 2015) - Hirano, Tomoko; Munnik, Teun; Sato, Masa H.
Abstract : Phosphatidylinositol 3-phosphate 5-kinase is essential for the endosome maturation and cortical microtubule associations for PIN protein trafficking in young root cortical and stele cells. Abstract: Phosphatidylinositol 3, 5-bisphosphate [PtdIns(3, 5)P2 ] is an important lipid in membrane trafficking in animal and yeast systems; however, its role is still largely obscure in plants. Here, we demonstrate that the phosphatidylinositol 3-phosphate 5-kinase, formation of aploid and binucleate cells1 (FAB1)/FYVE finger-containing phosphoinositide kinase (PIKfyve), and its product, PtdIns(3, 5)P2, are essential for the maturation process of endosomes to mediate cortical microtubule association of endosomes, thereby controlling proper PIN-FORMED protein trafficking in young cortical and stele cells of root. We found that FAB1 predominantly localizes on the Sorting Nexin1 (SNX1)-residing late endosomes, and a loss of FAB1 function causes the release of late endosomal proteins, Ara7, and SNX1 from the endosome membrane, indicating that FAB1, or its product PtdIns(3, 5)P2, mediates the maturation process of the late endosomes. We also found that loss of FAB1 function causes the release of endosomes from cortical microtubules and disturbs proper cortical microtubule organization.